IMPLEMENTASI ALGORITMA ENKRIPSI CITRA DIGITAL BERBASIS CHAOS MENGGUNAKAN FUNGSI KOMPOSISI LOGISTIC DAN GAUSS ITERATED MAP - Suci Boru Kembaren; Suryadi Suryadi; Triswanto Triswanto (Universitas Muhammadiyah Semarang, 2018)
Computer and information technology is very fast as technology develops. People can easily use the internet as a media for searching, sending and receiving information. Information can be in the form of text, image, audio, video, and multimedia, information can be quickly spread throughout the world through the internet. To increase the durability of the algorithm used in the encryption process from brute force attacks, one of them is by implementing chaos theory. The aim of the study was to create a digital image encryption algorithm based on chaos function. The chaos function used is the result of the composition of the Logistic Map function and the Gauss Map function. The chaos function will be used to generate a key stream that will be used to substitute the original image pixel into an encrypted image with XOR operations. The simulation results show that the key sensitivity of this algorithm is that up to 10-16 and the key space is the key is 1.8 x 1079. The NIST test was performed and proved that the resulting key stream was random, and from the histogram test the pixel value of the uniform encryption image. This shows that the digital image encryption algorithm with the Log-gauss Map function is resistant to brute force and statistical attacks. PSNR test results for all original images with the results of the description of the same pixel values . Keywords: Enkripsi, Chaos, Citra digital, Kriptografi, Log-gauss Map, Logistic Map, Gauss Iterated Map